A kind of fluidized solidified slag and preparation method thereof
By using construction slag and industrial solid waste as materials, combined with appropriate dispersants and water, fluid solid slag is prepared, which solves the environmental pollution and construction complexity of construction slag backfill, and achieves the goals of efficient resource utilization and low-carbon and environmental protection.
Patent Information
- Application Number
- CN202411613974.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing construction waste backfill technology has environmental pollution, engineering safety hazards and construction complexity problems. The production of traditional curing agents will produce a large amount of CO2 and fine dust, which is very costly.
Construction slag is used as the base material, combined with industrial solid waste such as calcium carbide slag, fly ash and ore powder as the curing agent, and suitable dispersants such as sodium silicate powder and rice husk ash are added. After stirring evenly, water is added to prepare fluid solidified slag.
It realizes efficient resource utilization of building slag, reduces construction complexity and environmental pollution, improves the mechanical properties and water stability of fluid solidified slag, and meets the needs of foundation backfill and road base materials.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of resource utilization of construction waste and industrial solid waste, and specifically to a fluidized solidified slag and a preparation method thereof. Background Art
[0002] With urbanization and large-scale renovation of old urban areas, the amount of construction waste, one of the building wastes, is increasing. The current resource utilization rate of construction waste is low, and the main disposal methods are stacking and filling, which pose great environmental and safety risks. How to reasonably utilize construction waste as a resource has become a focus of social attention and is the key to solving the problem of construction waste disposal.
[0003] The traditional foundation backfill method mainly uses cement soil, fly ash soil and other materials for layered rolling and compaction. The construction is complex, time-consuming, and has high environmental and economic costs, and has high requirements for the construction operation surface. If you encounter narrow, special-shaped foundation trenches and pits with large backfill depths, as well as complex supporting structures or pipeline lines, the backfill quality, safety, economic and environmental costs are more difficult to control. Using fluidized solidified soil for the above backfill is a convenient and feasible technical approach. Utilize engineering waste soil locally, add curing agent and water, and no vibration is required. It can meet the requirements of pumping or even self-leveling. After maintenance, it has a certain strength and water stability to meet the needs of foundation backfill. It can also be used as a road base material, especially suitable for backfilling narrow foundation trenches and laying pipelines.
[0004] Using construction waste as backfill soil not only disposes of the construction waste, but also avoids the problem of too high natural moisture content of sludge or high impurity content of poor geological soil. Currently, the commonly used inorganic curing agents are cement and lime, and their production will produce a large amount of CO 2 The high environmental cost is contrary to the concept of low-carbon and environmental protection. Organic curing agents and ionic curing agents form strength quickly, but the preparation cost is high, and the mechanical properties tend to deteriorate in the later stage. Using general industrial solid waste rich in aluminosilicate as a curing agent, in an alkaline environment, it will produce gels such as calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH) to promote the generation of strength. It has certain theoretical feasibility, low cost and conforms to the concept of low-carbon and environmental protection.
[0005] The Chinese invention patent with the announcement number CN115403352B discloses a method for preparing fluidized solidified soil using construction waste. The fluidized solidified soil components include construction waste and admixtures. The admixture components used include, by weight, 25-35% fly ash, 25-30% slag, 5-15% quicklime, 10-20% calcined kaolin, 2-5% sodium silicate, 1-3% sodium sulfate, and 1-2% polyether silicone defoamer; the ratio of construction waste, admixture and water is 35:10:55. The fluidized solidified soil uses a wide variety of curing agent raw materials and a large amount. Among them, sodium silicate and sodium sulfate are used as alkali activators, which are relatively expensive, and quicklime and calcined kaolin will produce a large amount of CO during production. 2 And fine dust, polluting the environment.
[0006] The present invention aims to solve the deficiencies in the prior art, strictly screens the composition and dosage of the curing agent, greatly reduces the pollution to the environment during the preparation process, and saves energy and cost. Screening the types of dispersants helps to evenly distribute the slag particles and the curing agent, ensures the uniform microstructure of the cured soil, and thus improves the overall performance of the cured soil. At the same time, the preparation process is simple and convenient, and the fluidized cured slag obtained has high fluidity, moderate viscosity, and low water seepage rate, which meets the requirements of pumping and even self-leveling; it has a large wet density, excellent mechanical properties and water stability: the setting time is short, and the construction efficiency is improved. At the same time, it saves construction costs, has little pollution to the environment, and solves the problems of narrow foundation trenches and pipeline laying faced by soil backfill. Summary of the invention
[0007] In order to improve the resource utilization of construction waste and solve the technical complexity and quality problems of existing narrow foundation trench backfill, the purpose of this application is to provide a fluidized solidified waste, using the crushed construction waste as the base material, and using three industrial solid waste solidifiers: calcium carbide slag, fly ash and mineral powder. The main component of calcium carbide slag is Ca(OH) 2 , can provide an alkaline environment. Slag and fly ash contain a large amount of silicon oxide (SiO 2 ), calcium oxide (CaO) and aluminum oxide (Al 2 O 3 ), which can react with volcanic ash in an alkaline environment to generate C-(A)-SH gel to consolidate soil particles, fill and compact pores, and improve the mechanical properties of solidified slag. While preparing fluidized solidified slag with excellent performance, it solves the current problems of large output of construction slag, environmental pollution and engineering safety, and rationally reuses three industrial solid wastes: carbide slag, slag and fly ash.
[0008] Suitable dispersants were screened to help evenly distribute the slag particles and the curing agent, ensuring a uniform microstructure of the cured soil, thereby improving the overall performance of the cured soil.
[0009] The technical solutions adopted in this application are as follows:
[0010] A fluidized solidified slag, comprising: construction slag, a solidifying agent, a dispersant and water;
[0011] The above-mentioned construction waste is calculated by weight, and the amount of construction waste material used is 100 parts.
[0012] The construction waste refers to the sieve material after crushing and screening of demolished brick-concrete structures. In the naturally air-dried state, the maximum particle size is 4.75 mm and the organic matter content does not exceed 5%.
[0013] The above-mentioned curing agent uses general industrial solid waste, including: carbide slag powder, mineral powder and fly ash;
[0014] The above dispersants are sodium silicate powder and rice husk ash, and the proportions of the two are respectively: 2-3 parts of sodium silicate powder and 6-7 parts of rice husk ash.
[0015] Among them, the silicon oxide (SiO 2 ) and sodium oxide (Na 2 The ratio of silicon dioxide to sodium oxide is usually expressed by a modulus (M), which is the molar ratio of silicon dioxide to sodium oxide. The present invention uses sodium silicate powder with a modulus of 2.80, that is, for every mole of sodium oxide in the sodium silicate powder, there are 2.80 moles of silicon dioxide.
[0016] Furthermore, by weight, the carbide slag powder is 2-4 parts, the mineral powder is 4-10 parts and the fly ash is 2-8 parts, the carbide slag powder is the product of grinding the carbide slag, and the standard mesh number is 400-600 mesh; the mineral powder is S95 grade granulated blast furnace slag; the fly ash is grade II ash. Among them, the sodium silicate powder and rice husk ash are passed through a coarse screen and become powder.
[0017] The water used is 36 to 42 parts by weight.
[0018] The present application provides a fluidized solidified slag, characterized in that it is prepared by preparing the following raw materials: 100 parts of construction slag, 2 to 4 parts of carbide slag powder, 4 to 10 parts of mineral powder, 2 to 8 parts of fly ash, 2 to 3 parts of sodium silicate powder, 6 to 7 parts of rice husk ash, and 36 to 42 parts of water.
[0019] Furthermore, the carbide slag powder is a product of grinding carbide slag, with a standard mesh number of 400-600 meshes; the mineral powder is S95 grade granulated blast furnace slag; the fly ash is grade II ash. Sodium silicate powder and rice husk ash are passed through a coarse screen and become powder.
[0020] The present application also provides a method for preparing fluidized solidified slag: the method comprises the following steps: weighing carbide slag powder, mineral powder, fly ash, construction slag, sodium silicate powder, rice husk ash and water for use; putting carbide slag powder, mineral powder, fly ash, sodium silicate powder and rice husk ash into a blender and stirring evenly to obtain a mixture A; putting the construction slag and the mixture A into the blender together, and adding 80% of the total mass of the required water, stirring for 180 seconds to obtain a mixture B; adding the remaining 20% of water to the mixture B, stirring for 120 seconds, and obtaining the mixed fluidized solidified slag.
[0021] During the stirring process, the stirring rate is 150-200 r / min.
[0022] The prepared fluidized solidified soil is characterized in that the wet density of the fluidized solidified soil is 1760-1910 kg / m 3 The fluidity is 181-220 mm, the viscosity is 2900-3800 mPa·s, the water seepage rate is 1.8-2.7%, the initial setting time and final setting time are 5.5-9 h and 9.5-14 h respectively, the 28d compressive strength is 6.3-8.5 MPa, and the water stability coefficient is 0.86-0.94.
[0023] Compared with the prior art, the beneficial effects of this application are:
[0024] 1) The use of fluidized solidified soil for backfilling in this application is a convenient and feasible technical approach. It utilizes construction waste soil locally, adds curing agent and water, and does not require vibration. It can meet the requirements of pumping or even self-leveling. After maintenance, it has a certain strength and water stability, which meets the basic needs of foundation backfilling. It can also be used as a road base material, especially suitable for backfilling narrow foundation trenches and laying pipelines.
[0025] 2) The base material used for fluidized solidified soil in this application is construction waste soil, which is the screened material after crushing and screening of demolished brick-concrete structures; using construction waste soil as the base material to prepare fluidized solidified soil not only disposes of the construction waste soil, but also avoids the problem of too high natural moisture content of sludge or high impurity content of poor geological soil.
[0026] 3) The curing agent used in the present application for fluidized solidified slag is selected from three general industrial solid wastes: calcium carbide slag powder, mineral powder and fly ash. The main component of calcium carbide slag is Ca(OH) 2 , can provide an alkaline environment. Slag and fly ash contain a large amount of silicon oxide (SiO 2 ), calcium oxide (CaO) and aluminum oxide (Al 2 O 3 ), which can undergo a volcanic ash reaction in an alkaline environment to generate C-(A)-SH gel to consolidate soil particles, fill and compact the pores, and improve the mechanical properties of fluidized solidified slag.
[0027] 4) This application effectively utilizes construction waste, effectively alleviating environmental pollution and engineering safety issues caused by the stacking of construction waste. Using general industrial solid waste as a curing agent reduces CO2 emissions during the production process compared to inorganic curing agents such as cement and lime. 2 The emission of fine dust is in line with the concept of low carbon and environmental protection. Compared with organic and ionic curing agents, the performance of construction waste solidified by general industrial solid waste is more stable. In addition, the reuse of construction waste and general industrial solid waste can also save economic costs.
[0028] 5) This application screens the types of dispersants, and the screened dispersants help to evenly distribute the slag particles and the curing agent, ensure the uniform microstructure of the cured soil, and thus improve the overall performance of the cured soil. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a flow chart of the preparation process for fluidized solidified slag used in this application. DETAILED DESCRIPTION
[0030] The present invention is further described below by specific examples and comparative examples. However, it should be understood that these examples and comparative examples are only used for more detailed and specific description and should not be construed as limiting the present invention in any form.
[0031] Example 1
[0032] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0033] By weight: 100 parts of construction waste, 2 parts of calcium carbide slag powder, 6 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 2 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water;
[0034] The preparation process of fluidized solidified slag provided in this embodiment is as follows:
[0035] Weigh the mass of each component material according to mass;
[0036] ② The carbide slag powder, mineral powder, fly ash, sodium silicate powder, rice husk ash was mixed in a blender to obtain a mixture A;
[0037] ③ Put the construction waste and mixture A into a mixer, add 80% of the total water, and stir for 180 seconds to obtain mixture B.
[0038] ④ Add the remaining 20% water to mixture B and stir for 120 seconds to obtain the fluidized solidified soil.
[0039] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1860 kg / m 3, fluidity 220 mm, viscosity 2900 mPa·s, water bleeding rate 2.6%, initial setting time and final setting time 9 h and 14 h respectively.
[0040] After pouring into the mold and curing at room temperature for 24 hours, the mold was demoulded and then standardly cured for 28 days. The compressive strength and water stability were tested. The 28-day compressive strength was 7.0 MPa and the water stability coefficient was 0.90.
[0041] Example 2
[0042] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0043] By weight: 100 parts of construction waste, 4 parts of calcium carbide slag powder, 6 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 2 parts of sodium silicate powder, 7 parts of rice husk ash, and 38 parts of water;
[0044] The process for preparing fluidized solidified slag provided in this embodiment is the same as that in embodiment 1.
[0045] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1880 kg / m 3 , fluidity 212 mm, viscosity 3000 mPa·s, water bleeding rate 2.3%, initial setting time and final setting time 8 h and 13 h respectively.
[0046] After pouring into the mold and curing at room temperature for 24 hours, the mold was demoulded and then standardly cured for 28 days. The compressive strength and water stability were tested. The 28-day compressive strength was 7.4MPa and the water stability coefficient was 0.90.
[0047] Example 3
[0048] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0049] By weight: 100 parts of construction waste, 4 parts of calcium carbide slag powder, 6 parts of S95 grade mineral powder, 2 parts of grade II fly ash, 3 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water;
[0050] The process for preparing fluidized solidified slag provided in this embodiment is the same as that in embodiment 1.
[0051] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1860 kg / m 3 , fluidity 210 mm, viscosity 3000 mPa·s, water bleeding rate 2.7%, initial setting time and final setting time 7.5 h and 13 h respectively.
[0052] The cast steel was demolded after 24 h of room temperature curing and then standard curing for 28 days before testing its compressive strength and water stability. The 28-day compressive strength was 6.8 MPa and the water stability coefficient was 0.94.
[0053] Example 4
[0054] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0055] By weight: 100 parts of construction waste, 4 parts of calcium carbide slag powder, 6 parts of S95 grade mineral powder, 8 parts of grade II fly ash, 3 parts of sodium silicate powder, 7 parts of rice husk ash, and 38 parts of water;
[0056] The process for preparing fluidized solidified slag provided in this embodiment is the same as that in embodiment 1.
[0057] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1900 kg / m 3 , fluidity 205 mm, viscosity 3300 mPa·s, water bleeding rate 2.0 %, initial setting time and final setting time 8.5 h and 14 h respectively.
[0058] The cast steel was demolded after 24 h of room temperature curing and then standard curing for 28 days before testing its compressive strength and water stability. The 28-day compressive strength was 6.6 MPa and the water stability coefficient was 0.92.
[0059] Example 5
[0060] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0061] By weight: 100 parts of construction waste, 4 parts of calcium carbide slag powder, 4 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 3 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water;
[0062] The process for preparing fluidized solidified slag provided in this embodiment is the same as that in embodiment 1.
[0063] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1870 kg / m 3 , fluidity 205 mm, viscosity 3000 mPa·s, water bleeding rate 2.6%, initial setting time and final setting time 9 h and 13.5 h respectively.
[0064] The cast steel was demolded after 24 h of room temperature curing and then standard curing for 28 days before testing its compressive strength and water stability. The 28-day compressive strength was 8.0 MPa and the water stability coefficient was 0.86.
[0065] Example 6
[0066] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0067] By weight: 100 parts of construction waste, 4 parts of calcium carbide slag powder, 10 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 2 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water;
[0068] The process for preparing fluidized solidified slag provided in this embodiment is the same as that in embodiment 1.
[0069] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1890 kg / m 3 , fluidity 195 mm, viscosity 3300 mPa·s, water bleeding rate 1.9 %, initial setting time and final setting time 6 h and 9.5 h respectively.
[0070] After pouring into the mold and curing at room temperature for 24 hours, the mold was demoulded and then standardly cured for 28 days. The compressive strength and water stability were tested. The 28-day compressive strength was 8.5 MPa and the water stability coefficient was 0.90.
[0071] Example 7
[0072] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0073] By weight, 100 parts of construction waste, 4 parts of calcium carbide slag powder, 8 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 2 parts of sodium silicate powder, 7 parts of rice husk ash, and 36 parts of water;
[0074] The process for preparing fluidized solidified slag provided in this embodiment is the same as that in embodiment 1.
[0075] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1910 kg / m 3 , fluidity 181mm, viscosity 3800 mPa·s, water bleeding rate 1.8%, initial setting time and final setting time 5.5 h and 10 h respectively.
[0076] The cast steel was demoulded after 24 h of room temperature curing and then standard curing for 28 days before testing its compressive strength and water stability. The 28-day compressive strength was 7.7 MPa and the water stability coefficient was 0.89.
[0077] Example 8
[0078] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0079] By weight: 100 parts of construction waste, 4 parts of calcium carbide slag powder, 8 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 3 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water;
[0080] The process for preparing fluidized solidified slag provided in this embodiment is the same as that in embodiment 1.
[0081] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1870 kg / m 3 , fluidity 202 mm, viscosity 3200 mPa·s, water bleeding rate 2.2%, initial setting time and final setting time 6 h and 10 h respectively.
[0082] The cast steel was demoulded after 24 h of room temperature curing and then standard curing for 28 days before testing its compressive strength and water stability. The 28-day compressive strength was 7.1 MPa and the water stability coefficient was 0.91.
[0083] Example 9
[0084] This embodiment provides a fluidized solidified slag, and the preparation materials thereof are as follows:
[0085] By weight, 100 parts of construction waste, 4 parts of calcium carbide slag powder, 8 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 3 parts of sodium silicate powder, 7 parts of rice husk ash, and 42 parts of water;
[0086] The process for preparing fluidized solidified slag provided in this embodiment is the same as that in embodiment 1.
[0087] The fluidized solidified soil mixture obtained in this embodiment has a wet density of 1760 kg / m 3 , fluidity 213 mm, viscosity 3100 mPa·s, water bleeding rate 2.1%, initial setting and final setting time 8 h and 12.5 h respectively.
[0088] The cast steel was demoulded after 24 h of room temperature curing and then standard curing for 28 days before testing its compressive strength and water stability. The 28-day compressive strength was 6.3 MPa and the water stability coefficient was 0.93.
[0089] The performance of the fluidized solidified soil of Examples 1-9 is summarized in Table 1.
[0090] Table 1: Summary of properties of fluidized solidified soil of Examples 1-9
[0091]
[0092] As can be seen from Table 1, the fluidized solidified slag prepared in the embodiment of the present application has a wet density that meets the requirements for solidified soil filling; the fluidity and viscosity both meet the requirements for pumping or even self-leveling; the water seepage rate is low; the 28-day compressive strength is high; the water stability coefficient is above 0.86 and the final setting is within 14 hours.
[0093] Example 10
[0094] This embodiment is an example of screening the components and dosage ratio of the curing agent in fluidized solidified slag.
[0095] Experimental purpose: To investigate the effects of the components and dosage ratio of the curing agent for fluidized solidified soil on the performance of fluidized solidified soil.
[0096] Experimental group 1: composition and preparation method of Example 1.
[0097] Experimental group 2: composition and preparation method of Example 6.
[0098] Control group 1: The mineral powder in Example 1 was removed, and the original 6 parts were distributed to carbide slag powder and grade II fly ash in proportion, that is, the composition was: 100 parts of construction waste, 4 parts of carbide slag powder, 8 parts of grade II fly ash, 2 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water; the preparation method was the same as that in Example 1.
[0099] Control group 2: The carbide slag powder in Example 1 was removed, and the original 2 parts were evenly distributed to S95 grade mineral powder and Class II fly ash, that is, the composition was: 100 parts of construction waste, 7 parts of S95 grade mineral powder, 5 parts of Class II fly ash, 2 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water; the preparation method was the same as Example 1.
[0100] Control group 3: On the basis of Example 1, the amount of carbide slag powder was increased, calculated by weight, 100 parts of construction waste, 10 parts of carbide slag powder, 6 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 2 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water; the preparation method was the same as Example 1.
[0101] Control group 4: Based on Example 1, the amount of mineral powder was reduced. By weight, the following ingredients were used: 100 parts of construction waste, 2 parts of calcium carbide slag powder, 2 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 2 parts of sodium silicate powder, 6 parts of rice husk ash, and 38 parts of water. The preparation method was the same as that of Example 1.
[0102] The specific components and dosage of the above experimental group and control group are shown in Table 2
[0103]
[0104] Table 2: Specific components and dosage of each group (parts)
[0105] The performance summary of the fluidized solidified slag in the above experimental group and control group is shown in Table 3. Among them, experimental group 1 and experimental group 2 are no longer measured repeatedly, and the relevant data of the previous measurement are used. The experimental conditions of the control group are consistent with those of the experimental group.
[0106] Table 3: Summary of properties of fluidized solidified soil in the experimental group and the control group
[0107]
[0108] From the above values, it can be seen that the control group 2 lacks carbide slag powder, that is, lacks the key substance that can provide an alkaline environment, resulting in no volcanic ash reaction between the above substances. Therefore, the prepared fluidized solidified slag cannot solidify for a long time.
[0109] Control group 1 lacks mineral powder, resulting in serious deviations of its viscosity, water seepage rate, initial setting time, final setting time, etc. from normal values. It can be inferred that although carbide slag powder and fly ash can react to a certain extent to act as a curing agent, the curing agent obtained by the reaction of the two does not achieve the expected curing effect. Among them, the 28d compressive strength is only 2.1 Mpa.
[0110] In the control group 3, due to the presence of excessive carbide slag powder, the fluidized solidified slag solidified too quickly and could not meet the actual use requirements, and its 28d compressive strength did not reach the optimal effect range.
[0111] The amount of mineral powder was reduced in the control group 4, which showed a similar pattern to the control group 1. That is, the reduction of mineral powder caused an imbalance in the composition ratio of the curing agent, and the internal reaction was not fully carried out, which ultimately resulted in the initial setting time, final setting time, 28d compressive strength, etc. failing to meet the requirements.
[0112] It can be seen that the composition and dosage ratio of the curing agent affect the performance of the fluidized solidified slag. The composition and dosage ratio of the curing agent and the composition and dosage ratio of the fluidized solidified slag in this application can achieve the optimal performance of the fluidized solidified slag and meet the needs of industrial use.
[0113] Embodiment 11
[0114] This embodiment is an example of screening the components and dosage ratio of the dispersant in fluidized solidified slag.
[0115] Experimental purpose: To investigate the effects of the components and dosage ratio of the dispersant for fluidized solidified soil on the performance of fluidized solidified soil.
[0116] Experimental method: The types and dosages of conventional dispersants were screened, and the 28d compressive strength and microstructural uniformity of the fluidized solidified slag after coagulation were compared. The microstructural uniformity includes the surface uniformity and the internal uniformity after the structure is destroyed after coagulation.
[0117] Experimental group 1: composition and preparation method of Example 1.
[0118] Control group 1: 100 parts of construction waste soil, 2 parts of carbide slag powder, 6 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 8 parts of sodium silicate powder, and 38 parts of water; the preparation method is the same as that of Example 1.
[0119] Control group 2: 100 parts of construction waste soil, 2 parts of calcium carbide slag powder, 6 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 8 parts of rice husk ash, and 38 parts of water; the preparation method is the same as that of Example 1.
[0120] Control group 3: 100 parts of construction waste soil, 2 parts of calcium carbide slag powder, 6 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 8 parts of sodium pyrophosphate, and 38 parts of water; the preparation method is the same as that of Example 1.
[0121] Control group 4: 100 parts of construction waste soil, 2 parts of carbide slag powder, 6 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 6 parts of sodium silicate powder, 2 parts of rice husk ash, and 38 parts of water; the preparation method is the same as that of Example 1.
[0122] Control group 5: 100 parts of construction waste soil, 2 parts of carbide slag powder, 6 parts of S95 grade mineral powder, 4 parts of grade II fly ash, 8 parts of steel slag powder, and 38 parts of water; the preparation method is the same as that of Example 1.
[0123] The performance summary of the fluidized solidified soil in the experimental group and the control group is shown in Table 4. Among them, the experimental group 1 used the samples prepared in the early stage, and the experimental conditions of the control group were consistent with those of the experimental group.
[0124] Table 4: Summary of properties of fluidized solidified soil in the experimental group and the control group
[0125]
[0126] It can be seen from Table 4 that the type and amount of dispersant have a certain influence on the 28d compressive strength, but the overall influence is not significant. However, it has a greater influence on the surface uniformity and internal uniformity of the fluidized solidified slag after solidification. When the dispersants sodium silicate powder, rice husk ash, sodium pyrophosphate and steel slag powder are used alone, the surface uniformity and internal uniformity of the fluidized solidified slag obtained are not uniform and fine, and almost pore-free. The fluidized solidified slag obtained by using a specific proportion of sodium silicate powder and rice husk ash is uniform and fine, and almost pore-free. At the same time, the ratio of the two also affects the uniformity of the fluidized solidified slag.
[0127] Without departing from the scope of the present invention, those of ordinary skill in the art may modify and change the present invention. In addition, it should be understood that the aspects of each embodiment can be interchanged as a whole or in part. The above description is also only exemplary and is not intended to limit the present invention further described in the appended claims.
Claims
1. A fluidized solidified soil, characterized in that: It is prepared from the following raw materials: construction debris, curing agent, dispersant and water; the curing agent is general industrial solid waste, specifically: carbide slag powder, mineral powder and fly ash; the dispersant is sodium silicate powder and rice husk ash; among them, 100 parts of construction debris, 2-4 parts of carbide slag powder, 4-10 parts of mineral powder, 2-8 parts of fly ash, 2-3 parts of sodium silicate powder, 6-7 parts of rice husk ash, and 36-42 parts of water.
2. The fluidized solidified soil according to claim 1, characterized in that: The construction waste refers to the sieves after crushing and screening of demolished brick-concrete structures. In the naturally air-dried state, the maximum particle size is 4.75 mm and the organic matter content does not exceed 5%.
3. The fluidized solidified soil according to claim 2, characterized in that: The carbide slag powder is the product of grinding carbide slag, and the standard mesh number is 400-600 mesh; the mineral powder is S95 grade granulated blast furnace slag; the fly ash is grade II ash; sodium silicate powder and rice husk ash are passed through a coarse sieve to become powder, and the modulus of the sodium silicate powder is 2.
80.
4. The method for preparing fluidized solidified soil according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: weighing carbide slag powder, mineral powder, fly ash, construction waste soil, sodium silicate powder, rice husk ash and water for later use; putting the carbide slag powder, mineral powder, fly ash, sodium silicate powder and rice husk ash into a blender and stirring them evenly to obtain a mixture A; putting the construction waste soil and the mixture A into the blender together, adding 80% of the total mass of the required water, stirring for 180 seconds to obtain a mixture B; adding the remaining 20% of water into the mixture B, stirring for 120 seconds, and obtaining the mixed fluidized solidified waste soil.
5. The method for preparing fluidized solidified slag according to claim 4, characterized in that during the stirring process, the stirring rate is 150-200 r / min.
6. The method for preparing fluidized solidified soil according to claim 5, characterized in that: The wet density of the prepared fluidized solidified soil is 1760~1910kg / m 3 The fluidity is 181-220 mm, the viscosity is 2900-3800 mPa·s, the water seepage rate is 1.8-2.7%, the initial setting time and final setting time are 5.5-9 h and 9.5-14 h respectively, the 28d compressive strength is 6.3-8.5 MPa, and the water stability coefficient is 0.86-0.94.
Citation Information
Patent Citations
A method for preparing fluidized solidified soil using construction waste
CN115403352B
Alkali-activated solid waste composite high-flow-state solidified silt as well as preparation method and application thereof
CN118812204A